Responses of the African and American Equatorial Ionization Anomaly (EIA) to 2014 Arctic SSW Events - O. R. Idolor; A. O. Akala; O. S. Bolaji (Space Weather)
Abstract Aside from the influence of forcing from above on the ionosphere during space weather, forcing from below also have significant influence on the ionosphere. This study investigates responses of the equatorial ionization anomaly (EIA) in the African and American longitudinal sectors to the combined effects of 2014 Sudden Stratospheric Warming (SSW) events and geomagnetic storms that coexisted with them. The study locations cover ±40° geomagnetic latitudes in both sectors. A multiinstrument approach with models was adopted. During the SSW events, a hemispherical asymmetry in TEC distribution was observed, with higher plasma ionization in the Northern Hemisphere (NH). Generally, in both sectors, EIA crests locations shifted to higher latitudes during peak phases of SSW, except in the SH of the African sector, where crests locations shifted to lower latitudes. Reversal of stratospheric zonal mean wind direction supported reversed fountain effect. TEC responded positively to SSW peak phases and daytime or nighttime orientation of Prompt Penetration Electric Field (PPEF) and PPEF strength played major role on TEC responses to storms. PPEF values were generally weak, but comparatively higher in the American sector. TEC were predominant in the American sector than the African sector due to the comparative higher electrodynamics over the American sector. EIA crests were generally located at higher latitudes on the days of SSW peaks than on the days of geomagnetic storms, except in the NH of the American sector. In both sectors, geomagnetic storms modified ionospheric irregularities by weakening or enhancing them, while the major SSW event weakened irregularities.